2017
DOI: 10.1073/pnas.1713074114
|View full text |Cite
|
Sign up to set email alerts
|

GPCRs globally coevolved with receptor activity-modifying proteins, RAMPs

Abstract: Receptor activity-modifying proteins (RAMPs) are widely expressed in human tissues and, in some cases, have been shown to affect surface expression or ligand specificity of G-protein-coupled receptors (GPCRs). However, whether RAMP−GPCR interactions are widespread, and the nature of their functional consequences, remains largely unknown. In humans, there are three RAMPs and over 800 expressed GPCRs, making direct experimental approaches challenging. We analyzed relevant genomic data from all currently availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…All of the secretin-like receptors were included in the test set because this GPCR family encompasses the majority of GPCR-RAMP interactions described to date. Based on an earlier co-evolution and co-expression analyses we also included GPR4 and GPR182 from the rhodopsin-like GPCR family, and ADGRF5 from the adhesion GPCR family (14) . In addition, the chemokine cluster of GPCRs demonstrated significantly higher median co-expression with RAMP2 and RAMP3 in comparison with all GPCRs (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the secretin-like receptors were included in the test set because this GPCR family encompasses the majority of GPCR-RAMP interactions described to date. Based on an earlier co-evolution and co-expression analyses we also included GPR4 and GPR182 from the rhodopsin-like GPCR family, and ADGRF5 from the adhesion GPCR family (14) . In addition, the chemokine cluster of GPCRs demonstrated significantly higher median co-expression with RAMP2 and RAMP3 in comparison with all GPCRs (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence from disease-associated pathologies, tissue expression and knock out mice indicate that the breadth of GPCR-RAMP interactions is not yet fully appreciated (12, 13) . Furthermore, we demonstrated recently that GPCRs and RAMPs globally co-evolved and display correlated mRNA levels across human tissues, which suggests the likelihood for more widespread GPCR-RAMP interactions (14) . We also showed concordance between mRNA levels for a subset of GPCRs and RAMP2 using a single-cell MERFISH (multiplexed error reduced fluorescence in situ hybridization) method (15) .…”
Section: Introductionmentioning
confidence: 94%
“…However, these pleiotropic effects of RAMPs have mostly been studied in the context of a few receptors in the Family B/Secretin family, including the calcitonin receptor (CTR), secretin receptor, glucagon (6, 7), CRF 1 (8,9), and VPAC 1/2 (8) and the Family A receptors CaSR (10) and GPR30/GPER1 (11). The strong coevolution of RAMPs with most GPCR families suggests that they may have expanded interacting partners (12,13).…”
mentioning
confidence: 99%
“…with several other GPCRs (18), and a recent bioinformatics analysis suggested that RAMPs interact with more GPCRs than is currently appreciated (22). Understanding how the three peptides bind the receptors is especially important considering the phenomenon of signaling bias in which different ligands stabilize distinct receptor conformations to yield different downstream signaling outcomes (23).…”
mentioning
confidence: 99%